Neuromechanics of cycling: Opportunities for optimizing performance - Dorel, S.; Fohanno, V.; Boucher, M.; Rao, G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
From the very simple (external power output) to the more complex variables (effective force profile, index of effectiveness, specific joint power) up to a neuro-musculo-skeletal integrative approach, we will focus on the following items: a clear definition of each concepts and variables, the tools needed for its accurate measurement and the state of scientific knowledge (and/or illustration) about its potential interest for the cycling performance. The ultimate approach using musculoskeletal models will also be mentioned just to give an idea of the potential interest to use them in a cycling performance enhancement endeavor.